Peer and Self-assessment for Learners in Higher Level of Education - RACHMANIA, Rachmania (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
AbstractThere has been increasing interest in the use of peer and self-assessment for learners in universities. Such interest is mostly due to the awareness of the significant importance of the two kind of assessments toward students’ learning outcomes. Educators suggest that peer and self-assessment could encourage learners to be more responsible and reflective. This paper will investigate the definition of peer and self-assessment, evidences that could justify the effectiveness of peer and self-assessment, and  some numbers of principles of effective practice in the use of peer and self-assessment.